Impact of irrigation on livelihood and food security in the modern Hare River Irrigation Scheme in Southern Ethiopia - Christine, J.; Willibald, L.; Dominik, R.; Michael, H.; Awulachew, Seleshi Bekele; Hagos, Fitsum (2008)
The purpose of the undertaken study was to evaluate the impact that the modern Hare river irrigation scheme had on household food security as well as on lifestyle changes of the population in the study site Chano Chalba. This was done on the basis of the FAO food security pillars access to food, availability of food, utilization of food and the overall factor of food stability. RRA tools were used to conduct a before-after comparison, considering a ten years period. The quantitative data was analysed using SPSS and/or Excel and simple statistical measures such as cross tabulations, frequencies, percentages and means gave a visible overview of the outcomes. The modern irrigation scheme did not affect the livelihood and food situation directly but indirectly through other modernizations that came with and after the construction of the modern main canal, e.g. road, merchants, agricultural office, health centre, drinking water points, school, electricity etc. The major trigger was the introduction of a new banana type so that farmers changed from food crops to cash crops to earn a higher income. Following, the wealth situation of the population ameliorated but less food crops are produced and people become more dependent on the local market. The infrastructure of the study site developed in a positive way but still education, especially on food issues, are needed to have a sustainable repercussion and to secure people?s health and food situation. Further positive changes on the food situation could be able if the higher income was utilized more efficiently and if the construction of the modern irrigation scheme had been more appropriate and by incorporating the farmer?s requests.